Equine herpesvirus-1 genotype did not significantly affect clinical signs and disease outcome in 65 horses diagnosed with equine herpesvirus-1 myeloencephalopathy. (January 2020) - Pusterla, N.; Hatch, K.; Crossley, B.; Wademan, C.; Barnum, S.; Flynn, K.
Highlights: Equine herpesvirus-1 myeloencephalopathy (EHM) is a multifactorial disease, combining viral, host and environmental factors. EHM has been more commonly associated with the neuropathic (D752 ) than the non-neuropathic (N752 ) genotype. Horses with EHM caused by either D752 or N752 genotype of EHV-1 showed no differences in age, sex and outcome. Urinary incontinence was the only sign more frequently reported in horses infected with the D752 genotype of EHV-1. Abstract: The objective of this study was to determine if the genotype of equine herpesvirus-1 (EHV-1) impacted clinical disease and outcome of horses with laboratory confirmed equine herpesvirus myeloencephalopathy (EHM). Medical records from 65 horses diagnosed with EHM from 2011 to 2019 were reviewed for signalment, presence and severity of clinical signs (lethargy, fever, ataxia, urinary incontinence) and outcome. Horses were further grouped based on the EHV-1 genotype into neuropathic (D752 ) or non-neuropathic (N752 ) EHV-1 infection. Between the two EHV-1 genotype groups, age and sex distributions were similar, although breed distribution was different (Quarter Horses and Saddlebreds were overrepresented and Warmbloods were underrepresented in the EHV-1 D752 group compared to the EHV-1 N752 group; P = 0.009). Lethargy, fever, ataxia and outcome were not significantly different between the two EHV-1 genotype groups (P > 0.05). However, urinary incontinence was significantly more frequently reported in horses infected with the D752 genotype of EHV-1 (P=0.04). Contrary to previous studies, the present study showed no difference in frequency of genotype (D752 or N752 ) among 65 horses with EHM and, with the exception of urinary incontinence, no difference in clinical disease or outcome related to the EHV-1 genotype.